PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI PESANTREN MTI CANDUANG - Aldri Aldri; Zulfani Sesmiarni; Supratman Dzakir; Rafiqa Witri Asri; Ali Mustopa Yakub Simbolon; Ulma Devi (STKIP Pesisir Selatan, 2023)
Â The aim of this research is to investigate the impact of motivation and work discipline on teacher performance at MTI Canduang Islamic Boarding School. The study utilized a quantitative descriptive approach, with a sample size of 50 respondents selected through a questionnaire survey. The findings of the study revealed the following: 1) work motivation significantly influences teacher performance, 2) work discipline has a significant impact on teacher performance, and 3) there is a significant relationship between work motivation, work discipline, and teacher performance. The R2 analysis yielded a coefficient of determination (R2) value of 0.534 or 53.4%. This indicates that 53.4% of the variation in teacher performance at MTI Canduang can be explained by the independent variables of work discipline and work motivation. Furthermore, it was found that 33.1% of teacher performance at MTI Canduang is influenced by factors not considered in the research model.Keywords:Â Discipline, Work Motivation, Teacher Performance.